Almoravid Works on Defensive Architecture in Southeast Al-Andalus: Analysis of Their Remains and Proposal for Preventive Conservation - Marcos-Cobaleda, María; Gutiérrez Carrillo, María Lourdes (MDPI, 2021)
In the first half of the 12th century, several military works were developed throughout the territories under Almoravid rule, above all after 1126, both in the main towns and the rural areas of the Empire. Within this context, the aim of this paper is to present the results achieved in the framework of the PREFORTI R&D Project (BIA2015-69938-R) concerning the particular case of these military constructions built in the region of Southeast Al-Andalus (Granada and Almeria, Spain). To achieve this aim, we have studied their remains during field work, as well as documentation contained in archives, written sources and historiography, focusing on the risks that affect their conservation. The analysis of six cases of study has been included, where a sample of the systematic method based on preventive conservation measures has been detailed in two particular cases: the walls of the Alcazaba Qad¯ıma (Granada) and the walls of La Hoya and Cerro de San Cristóbal (Almeria). The proposed method has been validated by the public bodies responsible for the protection of this heritage. Its importance lies in the guarantee to slow down the deterioration of this heritage, which facilitates the implementation of effective and economic strategies for its conservation.
Keywords: Arquitectura militar; Granada; Almeria; Almoravids; Military constructions; First half of the 12th century; Risks of conservation